Sistem Monitoring Pendeteksi Suhu dan PH Air Tambak Menggunakan Metode Fuzzy - Widyastuti, Andini Regista; Amanda, Suristiani; Afriansyah, Riki; Riezky Pratiwi, Indah (Jurnal Inovasi Teknologi Terapan, 2024)
The snakehead fish is a type of freshwater fish that is widely cultivated due to its relatively high economic value. Achieving success in snakehead fish farming requires careful planning, effective management, understanding of cultivation techniques, and compliance with regulations and business requirements. However, temperature and pH checks in the fish pond at PT Mahkota Tanah Air are currently conducted manually. The environmental conditions of the pond significantly affect the freshwater fish farming process. Therefore, a modern technology-based detection system is needed to monitor the temperature and pH of the fish pond using the Fuzzy method. Thus, the implementation of this temperature and pH detection monitoring system can assist pond operators in monitoring the temperature and pH of the fish pond. The testing results of the temperature and pH sensors at PT Mahkota Tanah Air show an accuracy rate of 98%, indicating success.